Respuesta :

Step-by-step explanation:

1

[tex] \frac{1}{3 + 4i} \times \frac{3 - 4i}{3 - 4i} = \frac{3 - 4i}{25} = \frac{ 3}{25} - \frac{4i}{25} [/tex]

2)

[tex] \frac{1}{3 - 4i} \times \frac{3 + 4i}{3 + 4i} = \frac{3 + 4i}{25} = \frac{ 3}{25} + \frac{4i}{25} [/tex]

3)

1+0i

4)

[tex] \frac{3 - 4i}{3 + 4i} \times \frac{3 - 4i}{3 - 4i} = \frac{ - 7 - 24i}{25} = - \frac{7}{25} - \frac{24i}{25} [/tex]

5)

3 - 4i

6)

[tex] \frac{3 + 4i}{3 - 4i} \times \frac{3 + 4i}{3 + 4i} = \frac{ - 7 + 24i}{25} = - \frac{7}{25} + \frac{24i}{25} [/tex]